Investigating the genetics of sporadic early-onset Alzheimer’s disease using a customised genotyping chip - Barber, Imelda Stacey (2016)
Alzheimer’s disease (AD) is the commonest form of dementia and is characterised with neuropathological hallmarks such as aggregated amyloid plaques and hyper-phosphorylated tau protein. One type of AD is autosomal dominant AD (ADAD) which is caused by highly penetrant variants in one of three genes (APP, PSEN1 and PSEN2), other cases of AD are described as sporadic and can have a late onset of disease symptoms (> 65 years of age) or early onset (≤ 65 years or age). Late-onset Alzheimer’s disease (LOAD) is estimated to be 70% heritable and is common. Conversely sporadic early-onset Alzheimer’s disease (sEOAD) is estimated to 90% heritable but is relatively rare. The difference in prevalence between the two types of AD has resulted in genome wide association studies focusing on LOAD with sEOAD receiving little attention. Here we use an Illumina human exome genotyping chip customised with neurodegenerative markers (NeuroX) to genotype the coding region of sEOAD samples in a hope to elucidate the genetic aetiology of sEOAD.